An exhibition of theatre prints with a collection of sword (Kegan Paul, 1972)
In the Japanese blade this problem has been solved in a completely different way, by hardening only a part of the blade in a narrow strip along the cutting edge. This part of the blade, called the yakiba, is intensely hard and bears an extremely sharp cutting edge; the remainder of the blade is left comparatively soft, and being repeatedly folded during the forging provides a laminated and resilient support for the yakiba.